Geographical Variability of Mineral Elements and Stability of Restrictive Mineral Elements in Terrestrial Cyanobacteria Across Gradients of Climate, Soil, and Atmospheric Wet Deposition Mineral Concentration - Wang, Weibo; Li, Hua; Guénon, René; Yang, Yuyi; Shu, Xiao; Cheng, Xiaoli; Zhang, Quanfa (Frontiers in Microbiology, 2021)
Terrestrial cyanobacteria Nostoc commune is an ideal species to study the geographical variation of mineral elements of soil cyanobacteria at the species level. Here, we first address the following questions: 1) from where are these mineral elements, 2) are there geographical variations for these mineral elements, and if so, 3) which environmental factors drive the geographical variation of these mineral elements? Second, we tested whether the soil cyanobacterial mineral elements followed the “restrictive element stability hypothesis” of higher plants. Finally, we explored the effect of mineral geographic variation on ecological adaptation of soil cyanobacteria. We collected N. commune samples across gradients of climate, soil, and atmospheric wet deposition mineral concentration in mainland China. We measured fifteen minerals, including five macroelements (N, Ca, K, Fe, P), five microelements (Mn, Zn, Cu, Co, Se), and five heavy metals (Pb, Cr, As, Cd, Hg). We found that five elements (P, Cu, Zn, Co, Pb) had significant geographical variation. They increased as the distance from the equator increased and decreased as the distance from the prime meridian increased. Mean annual precipitation and mean annual temperature explained most of the variation. We did not find any significant correlations between the mineral element contents in N. commune and the minerals in soil and rainfall, except for P. There was no significant correlation between the variation coefficients of different elements and their actual detected contents and their potential physiological required contents. The statistical results of our experiment did not support the “restrictive element stability hypothesis”. We speculated that net accumulation of mineral elements in cyanobacterial cells and extracellular polysaccharides (EPS) might play an important role for terrestrial cyanobacteria in the adaptation to dry and cold conditions.